Helminth diseases of small ruminants in the tropics: A review of epidemiology and control strategies - Tembely, S.; Hansen, James (Australian Centre for International Agricultural Research, 1996)
The paper briefly reviews the epidemiology and control of helminth parasites of small ruminants of economic importance in the tropics. Epidemiological factors influencing seasonal availability and acquisition of nematiode larvae and metacercaria by sheep and goats on pasture are discussed. The pattern of faecal egg output with peaks most commonly observed during the wet season appeared to be well correlated with the adult worm burden within the hosts. The epidemiological consequences of periparturient rise in nematode faecal egg counts and arrested (hypobiotic) larvae as a manifestation of acquired immunity and/or as a result of prior exposure of climatic factors during the free-living stage and the implications for the control of nematode infections are reviewed. Alternative control methods under tropical climatic conditions are also addressed.